Hell bent [compact disc, unabridged] - Bardugo, Leigh (Macmillan Audio, 2022)
Alex Stern is determined to break Darlington out of hell, even if it costs her future. But Alex faces forces far beyond her control, and when faculty members begin to die off, she knows these aren't just accidents.